(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
Ixora predeepii, a new species of the family Rubiaceae from Southern Western Ghats, India is described and illustrated. It is allied to Ixora elongata Heyne ex D. Don in general appearance, but differs from the latter by its small habit, short peduncled congested inflorescence, small purplish white flowers with glabrous corolla and scarlet berry. Bangladesh J. Plant Taxon. 23(1): 65-69, 2016 (June)